The War on Landmines. Issue 1 (May 2018) - Baer, Christoph; Musch, Thomas; Rolfes, Ilona; Sachs, Jürgen
Abstract: Decades of guerilla warfare in Colombia have left behind a deadly legacy of thousands of landmines. Now a German‐Colombian partnership is developing new ways of detecting these often improvised devices. Innovative technologies such as these can help further the incipient peace process.